Visual Dominance and Auditory Challenges: Optimizing Quranic Memorization Learning Based on Students' Learning Styles - Popon Masriah; Fajar Syarip (Educazione: Journal of Education and Learning, 2025)
This study aims to describe the implementation of Tahfiz Al-Qur'an learning and analyze the audio-visual learning styles of students at SMAIT Darul Quran Putri Bogor. Employing a qualitative descriptive approach with a case study design, data were collected through in-depth interviews, observations, and documentation involving the principal, Tahfiz coordinators, instructors, and senior students. The findings reveal that the Tahfiz program is systematically implemented through daily, weekly, and annual activities integrating Tahsin, Tahfiz, and Tafhim. The study highlights a significant impact of learning styles on memorization progress; visual learners complete their memorization faster due to the alignment of current methods with their cognitive preferences. Conversely, auditory learners experience delayed progress primarily due to restricted access to audio facilities and electronic devices. While strong institutional support and student motivation act as key supporting factors, challenges persist, including fluctuating student discipline, inflexible instructional approaches, and inadequate facilities for diverse learning modalities. Consequently, the institution is planning to integrate digital learning devices to optimize the memorization process for all students.